FAKTOR DOMINAN DALAM KOMUNIKASI EFEKTIF DALAM TIMBANG TERIMA: MOTIVASI DAN KEPEMIMPINAN - Kristianingsih, Yustina; Astuti, Martha Sri; Setyawati, Emiliana Indah Eko; Adriana, Fransiska (Sekolah Tinggi Ilmu Kesehatan Katolik St. Vincentius a Paulo Surabaya, 2024)
Communication in health services must be easy to understand because it is related to the nature and behavior of different health workers involved in nursing care, so that staff, nurses and doctors must understand how communication can be applied in all situations. The phenomenon at the research site as a result of interviews found that communication is still lacking effective both among nurses and other health teams. This research aims to analyze the factors that influence effective communication regarding SBAR consideration. The research design used descriptive analysis with a population of executive nurses in inpatient rooms at private hospitals in Surabaya who fulfil the inclusion criteria. Sample collection used simple random sampling with a sample size of 41 respondents. Data were collected using the SBAR communication effectiveness and acceptance questionnaire which is valid and reliable. After the data was collected, a simple regression test was carried out and the results obtained were that the majority (85%) of respondents carried out effective communication and acceptance. The factors related to effective communication regarding SBAR acceptance in this research are motivation and leadership. Effective communication in SBAR consideration is very important to continue to be improved so that the nursing department of the private hospital at the research site can continue to motivate the implementing nurse and manager of unit to support each other in the application of effective communication in SBAR consideration.